(untitled) (Heritage, 2021)
Throughout history, the phenomenon of hearing impairment has been the subject of interest of altruists, philosophers, doctors, priests, teachers and pedagogues. Today, this phenomenon is approached from a multidisciplinary aspect: medical, special education, sociological, pedagogical, psychological, linguistic, cultural and technological, all off which have the communication of deaf and hard of hearing people as a thing in common. Different approaches in building communication systems for deaf have led to three basic groups of methods: nonverbal, oral and combined. This paper will present an analysis of the development and application of the oral method, which at a certain point in time played a significant role in the process of education and rehabilitation of the deaf, with special emphasis on methods of demutation, ie speech and language construction in the deaf.